Modeling effects of dexamethasone on disease progression of bone mineral density in collagen‐induced arthritic rats. Issue 5 (3rd August 2015) - Lon, Hoi‐Kei; DuBois, Debra C.; Earp, Justin C.; Almon, Richard R.; Jusko, William J.
Abstract: A mechanism‐based model was developed to characterize the crosstalk between proinflammatory cytokines, bone remodeling biomarkers, and bone mineral density (BMD) in collagen‐induced arthritic (CIA) rats. Male Lewis rats were divided into five groups: healthy control, CIA control, CIA receiving single 0.225 mg kg −1 subcutaneous (SC) dexamethasone (DEX), CIA receiving single 2.25 mg kg −1 SC DEX, and CIA receiving chronic 0.225 mg kg −1 SC DEX. The CIA rats underwent collagen induction at day 0 and DEX was injected at day 21 post‐induction. Disease activity was monitored throughout the study and rats were sacrificed at different time points for blood and paw collection. Protein concentrations of interleukin (IL)‐1 β, IL‐6, receptor activator of nuclear factor kappa‐B ligand (RANKL), osteoprotegerin (OPG), and tartrate‐resistant acid phosphatase 5b (TRACP‐5b) in paws were measured by enzyme‐linked immunosorbent assays (ELISA). Disease progression and DEX pharmacodynamic profiles of IL‐1 β, IL‐6, RANKL, and OPG were fitted simultaneously and parameters were sequentially applied to fit the TRACP‐5b and BMD data. The model was built according to the mechanisms reported in the literature and modeling was performed using ADAPT 5 software with naïve pooling. Time profiles of IL‐1 β and IL‐6 protein concentrations correlated with their mRNAs. The RANKL and OPG profiles matched previous findings in CIA rats. DEX inhibited the expressions of IL‐1 β, IL‐6, and RANKL, but did not alter OPG. TRACP‐5b was also inhibited by DEX. Model predictions suggested that anti‐IL‐1 β therapy and anti‐RANKL therapy would result in similar efficacy for prevention of bone loss among the cytokine antagonists.